PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL, SISTEM PENGENDALIAN INTERN DAN MOTIVASI KERJA TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Kasus Pada Organisasi Perangkat Daerah Provinsi Papua) - Vania Annissa Holle; Agustinus Salle; Mariolin Sanggenafa (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2019)
This research aims to analyze the influence of accrual-based accounting standard, internal control system, and motivation of work on the quality of financial statements. The population were in 34 departments in Papua Province. The samples of this study were 65 people. The research method was used purposive sampling with criterion are the heads and the staff of sub-divisions of finance who participating in making financial report. Data collection was done by distributing questionnaires directly to each departments in Province of Papua. The analysis technique was used multiple linear regression. This study concludes that accrual-based accounting standard, internal control system, and work motivation have positive and significant effect on the quality of financial statements